Weighting Comparative Analysis Using Fuzzy Logic and Rank Order Centroid (ROC) in the Simple Additive Weighting (SAW) Method - Alfin Ghazali; Poltak Sihombing; Muhammad Zarlis (CESS (Journal of Computer Engineering, System and Science), 2022)
Decision Support System Method which is often referred to as the weighted addition method, one of which is Simple Additive Weighting. But the value of the weights in this system is not officially the calculation used. Therefore, usually a number of researchers combine this method with other methods to be more precise and accurate in supporting their decisions. In this study, the authors compare the results of the SAW method between the weighting based on the Fuzzy Logic method and the weighting based on the Rank Order Centroid (ROC) method. The case studied was the number of student satisfaction with learning outcomes during the Covid-19 pandemic. The results obtained are the number of students who are declared satisfied with learning during the Covid-19 pandemic as many as 6 students for the weighting of the Fuzzy Logic method and 5 students for the weighting of the Rank Order Centroid (ROC) method.